2010
DOI: 10.2478/s11535-010-0019-z
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic mechanisms of the Walnut antidiabetic effect in mice

Abstract: The present study was designed to explore the mechanism of action of walnut (the seed of Juglans regia) leaf and ridge on hepatic glucose metabolism in diabetic mice. Experimental diabetes was induced by intravenous administration of streptozotocin (60 mg/kg) and confirmed with an increase of blood glucose, 90-100% of the control, 72 hours later. Isolated extracts from walnut leaf and ridges were administered in a single effective dose of 400 mg/kg orally. Firstly, blood glucose was determined every 1 hour unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…This finding may be indicative of regeneration of the beta cells [ 9 ]. According to the study by Kamyab et al [ 21 ] in mice, oral walnut leaf and ridge extracts significantly reduced liver pyruvate carboxykinase activity and increased liver glycogen phosphorylase activity. They concluded that walnut could reduce the blood glucose level by inhibiting hepatic gluconeogenesis and stimulating secretion of pancreatic insulin.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be indicative of regeneration of the beta cells [ 9 ]. According to the study by Kamyab et al [ 21 ] in mice, oral walnut leaf and ridge extracts significantly reduced liver pyruvate carboxykinase activity and increased liver glycogen phosphorylase activity. They concluded that walnut could reduce the blood glucose level by inhibiting hepatic gluconeogenesis and stimulating secretion of pancreatic insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Its leaves have shown a significant hypoglycemic effect in diabetic animals. Increase of hepatic glycogenolysis, decrease of gluconeogenesis, inhibition of glucose absorption from the intestine, and enhancing serum insulin are the proposed mechanisms for hypoglycemic effect of J. regia (Asgary et al, 2008;Kamyab et al, 2010;Jelodar, Mohsen, Shahram, 2007). Increase of insulin level can be mediated through regenerative actions of J. regia on pancreatic islets.…”
Section: Juglans Regiamentioning
confidence: 99%
“…Numerous experimental and clinical studies have documented beneficial effects of phytotherapy for managing diabetes (Ghorbani, 2013a,b). Antidiabetic effect of phytochemicals is mediated through different mechanisms such as decreasing glucose absorption from intestine, inhibiting glucose production in the liver, increasing glucose uptake by tissues, enhancing insulin secretion from beta cells, and/or increasing pancreatic tissue regeneration (Asgary et al, 2008;Kamyab et al, 2010;Jelodar, Mohsen, Shahram, 2007;Shafiee-Nick et al, 2011;Shafiee-Nick et al, 2012a). The current review focused on phytochemicals, the antidiabetic action of which has been proved, at least in part, by pancreatic beta cell protection or regeneration (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental and clinical studies have documented beneficial effects of phytotherapy for managing diabetes 7 . Antidiabetic effect of phytochemicals is mediated through different mechanisms such as decreasing glucose absorption from intestine, inhibiting glucose production in the liver, increasing glucose uptake by tissues, enhancing insulin secretion from beta cells, and/or increasing pancreatic tissue regeneration [28][29][30] .…”
Section: Effects Of Peanut Skin Extracts On Blood Glucose Level In Micementioning
confidence: 99%